THE INFLUENCE OF STUDENT PERCEPTION OF TEACHERSâ TEACHING SKILL AND INTEREST TO LEARN TO ECONOMIC LEARNING ACHIEVEMENT ON STUDENT CLASS XI IPS SMA N 1 LENGAYANG - -, Nusmaneli - (Pendidikan Ekonomi, 2014)
This study aims to analyze: 1) The influence of students perceptions about teachers teaching skills to the learning achievement of Economics at the class XI IPS Lengayang SMA N 1, 2) The influence of student interest in the learning achievement of Economics class XI IPS Lengayang SMA N 1, 3 ) the influence of students perceptions of teachers teaching skills and students interest in learning simultaneously on learning achievement of Economics in class XI IPS SMA N 1 Lengayang. When the study was conducted in early September 2014. The type of research used in this study was a descriptive study associative. The study population was all students in class XI IPS SMA N 1 Lengayang totaling 139 people. Sampling technique used proportional random sampling with a sample size of 103 people. Data analysis techniques are descriptive and inductive analysis with SPSS version 16.0.The results showed that: First There is a positive and significant influence between students perceptions of teachers teaching skills to the learning achievement of Economics at the class XI IPS SMA N 1 Lengayang based on the analysis of data obtained tcount> t table (10.608> 1.659), Second there is positive and significant influences of relationship between students interest in the learning achievement of Economics class XI 1IPS SMA N 1 Lengayang based on the analysis of data obtained tcount> ttable (2.148> 1.659), Third There is a positive and significant influence between students perceptions about teachers teaching skills and interests to learn simultaneously on learning achievement of Economics in class XI IPS SMA N 1 Lengayang based on data analysis of Fcount > Ftable (133.866> 3.08) with a significant value of 0.000 < Î± = 0.05. This means that Ha is accepted and H0 is rejected. Where obtained the coefficient of determination (Adjusted R Square) of 0.728. From these results, it is suggested the teachers to improve further skills to teach small groups and individuals in order to increase the optimal learning and increase student interest in learning to be more in terms of student invlovement in the learning process. Thus, it can improve learning achievement of Economics class XI IPS SMA N 1 Lengayang.